Estimating Optimum Growth-Maximizing Public Debt Threshold for Nepal - Bhatta, Gopal Prasad; Mishra, Anu (NRB Economic Review, 2020)
One of the common agenda of underdeveloped economies is to achieve a high and sustainable level of economic growth in the long run. Domestic and external borrowings are playing a crucial role in fulfilling the resource gap in the context of Nepal for a long period. A growing number of recent studies support the idea of a debt threshold level (turning point) above which debt starts reducing economic growth. This paper empirically investigates the relationship between economic growth and several other factors (investment, trade openness, population growth, domestic savings, and government debt) in the context of Nepal. The debt-growth relationship has been estimated by regression analysis and further explored the non-linear relationship between public debt and economic growth using time series annual data for the period of 1976-2019. The ARDL bound technique has been applied to estimate the short-run and the long run impact of debt on economic growth. Moreover, a quadratic bivariate model based on ARDL coefficients has been estimated to identify the growth maximizing level of debt. The estimated parameters confirm the optimum public debt to GDP ratio in the context of Nepal is 33 per cent. The policy implication of this finding for the Government of Nepal (GoN) is to ensure public debt management in line with the growth maximizing debt threshold. Further, a high level of trade deficits and government effectiveness in public sector management squeezes the fiscal space in utilizing adequate public debt in Nepal.